Case report: Post-thoracoscopy pendelluft monitoring - Xiao, Zhibin; Zhang, Na; Zhang, Xiajing; Lu, Wenjun; Gao, Changjun; Sun, Xude (Frontiers in Medicine, 2023)
Asynchronous alveolar ventilation is called pendelluft, which may induce lung injury in spontaneously breathing patients. We report a case that electrical impedance tomography (EIT) was used to assess the pendelluft in a post-thoracoscopy patient. The pendelluft amplitude was as high as 77.5% of the tidal variation. The average regional time shift was 0.5 s. The patient was instructed to adjust the breathing method, symptomatic treatment was performed, and the symptoms were improved. This is the first case reporting pendelluft in a post-thoracoscopy patient. Our case demonstrated that (1) pendelluft may occur in post-thoracoscopy patients and it effects lung function, and (2) early identification of affected patients and implementation of corresponding treatments could improve patient outcomes.